Analisis Pengaruh Kebijakan Pemerintah dalam Pengembangan Perbankan Syariah di Indonesia - Amalia, Fitri; Andrini, Rozi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to analyze the effect of government policies on the development of Islamic banking in Indonesia. As a country with the largest Muslim population in the world, Indonesia has great potential in developing Islamic banking in accordance with sharia principles. However, structural and regulatory challanges often become obstacles in optimizing this sector. This research uses a qualitative method with a descriptive analysis approach, which involves analyzing the policies issued of this study show that from the financial services authority (OJK), have had a positive impact on the growth of Islamic banking. However, there are some challenges, such as inadequate infrastructure and fierce competition with conventional banking, which hinder further development. The findings highlight the importance of the government’s commitment in strengthening regulations and support for the Islamic banking industry in order to compete in the domestic and international markets.